A multimodal analysis of political satire: Webcomics and GIFs in Post-Arab Spring Egypt - El-Farahaty, Hanem (Linguistica Antverpiensia, New Series – Themes in Translation Studies, 2019)
The Egyptian Revolution in 2011 and the protests known as “the Arab Spring” resulted in an increase in the number of comic writers and amateurs who use specialist software to mix modes digitally for novel sign-making (Gursimesk, 2016; Lankshear & Knobel, 2008). These people draw creative forms of satire, including but not limited to political webcomics and Graphics Interchange Formats (GIFs) which exist alongside political cartoons. This article aims to employ a multimodal analysis of a sample of Egyptian webcomics and GIFs in order to highlight how visual design elements complement each other, in an effort to support translators and/or readers/viewers in their interpretation of the images and, by extension, in their ability to make sense of reality. With this aim in mind, this article combines Serafini’s (2010) tripartite approach to perception, structure and ideology; Kress and van Leeuwen’s (2006) discussion of elements of visual design, and Genette’s and Maclean’s (1991) approach to paratext. The analysis will also be informed by interviews with the founders and co-founders of two Facebook pages, and with a cartoonist working for Almasry Alyoum newspaper. First, the article discusses briefly the translation of comics or webcomics and GIFs, particularly the challenges of translating political webcomics and GIFs into English. The theoretical framework and a case study are then discussed in the second part.